THE IMPACT OF LOCAL GOVERNMENT'S FINANCIAL PERFORMANCE ON ECONOMIC GROWTH, UNEMPLOYMENT, POVERTY - Runtunuwu, Prince Charles Heston; Mazelan, Norsaidatul (JURNAL ECONOMICA : Research of Economic And Economic Education, 2023)
The purpose of this study is to analyze whether financial performance in the form of independence ratios, effectiveness ratios, efficiency ratios have a positive effect on economic growth; and also to analyze the effect of economic growth on unemployment; as well as to see whether economic growth has an effect on poverty. The data is in the form of a time series during the period 2011-2021 so that the results of this study are the result of using the time series during that period. Sources of data were obtained from BPS and the Finance Department of Taliabu Regency. The analysis technique used in this study used statistical analysis using the SPSS version 20 for Windows program. The analytical tool used is multiple linear regression (multiple regression). The results of the first hypothesis test, it can be concluded that the financial performance area in the form of independence ratio has a negative and significant influence on economic growth . The results of the second hypothesis test show that there is a significant influence between Financial Performance in the form of Effectiveness Ratio to Economic Growth. The results of the third hypothesis test have a significant positive effect between Financial Performance in the form of Efficiency Ratio to Growth Economy. The results of the fourth hypothesis test show that there is no significant positive effect on economic growth Unemployment. The results of the fifth hypothesis test are found significant negative effect of Economic Growth on Poverty.